Correlation of Ultrasonography Guided Fine Needle Aspiration Cytology with Postoperative Histopathology in Diagnosis of Thyroid Nodule - Sayied, Md Jaber Al; Choudhury, A Allam; Bithi, Sonia Jahan; Biswas, Ashim Kumar; Majumder, Riashat Azim; Razzak, Md Abdur; Haque, Md Hasanul; Md Quamruzzaman, - (Bangladesh Journal of Otorhinolaryngology, 2021)
Background: Fine-needle aspiration cytology (FNAC) is recommended as a decisive diagnostic step in the workup of patients with nodular thyroid disease. Unfortunately, FNAC can miss malignancies in smaller and deeper nodule. Ultrasound guided FNAC (US-FNAC) can reduce this error in suspicious thyroid nodule. Objectives: To find out the correlation of USG guided FNAC with postoperative histopathology in diagnosis of thyroid nodule. Methods: After obtaining clearance and approval from Institutional Review Board, all 45 patients of thyroid nodule who were admitted in the Department of Otolaryngology – Head & Neck surgery of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from April 2017 to August 2018 and had fulfilled the inclusion and exclusion criteria were selected for the study. Each patient was assessed before surgery by USG guided FNAC and post operatively by histopathology. Results: In this study mean age of the respondents was 33.33 yearswith SD±10.84. Male female ration was 1:5.4. USG guided FNAC was reported by ‘The Bethesda System for Reporting Thyroid Cytopathology’ (TBS-RTC).Of the 45 specimens 2 samples were nondiagnostic or unsatisfactory (Class I), 26 samples were benign (Class II), 2 samples were showing Atypia of Undetermined Significance or Follicular lesion of Undetermined Significance (Class III), 6 were showing follicular neoplasm or suspicious for a follicular neoplasm (Class IV), 5 samples were suspicious for malignancy (Class V) and 4 samples were positive for malignancy (Class VI). On comparison of ultrasound guided FNAC with histopathology the sensitivity for correct diagnosis was 94%, specificity was 93%, positive predictive value was 88%, negative predictive value was 96% and accuracy was 93%. Pearson’s correlation coefficient was 0.85 which is very strong for positive relationship. Conclusion: USG guided FNAC is the most accurate method for diagnostic evaluation of thyroid nodules. Bangladesh J Otorhinolaryngol; April 2021; 27(1): 36-43